Advances in two-photon imaging for monitoring neural activity in behaving mice - Li, Ruifeng; Li, Nan; Zhu, Dongju; Shi, Kai; Shen, Shasha; Zhang, Yi (Frontiers in Neuroscience, 2025)
An essential goal in neuroscience is to establish a link between animal behavior and neural activity. Monitoring neural activity during behavior is enhanced by establishing simple and consistent behaviors associated with perceptual cues. In recent years, significant strides have been made in studying the neural activity of behaving mice, thanks to the concurrent advancements in imaging systems and the development of multiple indicators. This review summarizes the current applications and methodological advancements of two-photon imaging technology in the context of behavioral mouse studies and explores the broader potential for applying this technology in future research with behaving mice.